2021
DOI: 10.14336/ad.2021.0104
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Metabolic Insufficiency in Aging and Dementia

Abstract: Metabolic insufficiency and neuronal dysfunction occur in normal aging but is exaggerated in dementia and Alzheimer's disease (AD). Metabolic insufficiency includes factors important for both substrate supply and utilization in the brain. Metabolic insufficiency occurs through a number of serial mechanisms, particularly changes in cerebrovascular supply through blood vessel abnormalities (ie, small and large vessel vasculopathy, stroke), alterations in neurovascular coupling providing dynamic blood flow supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 158 publications
0
10
0
Order By: Relevance
“…Metabolic insufficiency in disease-related regions may be explained by neuronal loss due to the regional accumulation of metabolic waste and toxic proteins. 52 Cortical hypometabolism was reported to reflect tau pathology and predict TDP-43 status. 53,54 Thus, taken together, these findings suggests that regional glymphatic dysfunction may account more for the pathophysiology of bvFTD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic insufficiency in disease-related regions may be explained by neuronal loss due to the regional accumulation of metabolic waste and toxic proteins. 52 Cortical hypometabolism was reported to reflect tau pathology and predict TDP-43 status. 53,54 Thus, taken together, these findings suggests that regional glymphatic dysfunction may account more for the pathophysiology of bvFTD.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that aDTI‐ALPS was associated with metabolic activity in the anterior brain regions, including the frontal lobe, OFC, and rectus gyrus. Metabolic insufficiency in disease‐related regions may be explained by neuronal loss due to the regional accumulation of metabolic waste and toxic proteins 52 . Cortical hypometabolism was reported to reflect tau pathology and predict TDP‐43 status 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2012 Iliff et al [2012] the glymphatic pathway for cerebrospinal fluid flow through the murine brain was identified and suggested to be important for clearance of metabolic waste. Accumulation of metabolic waste is common in dementia Turner [2021], Jack Jr et al 2018] and is suggested to be caused by a malfunctioning glymphatic pathway. The glymphatic system and its pathways have been detailed in mice.…”
Section: Introductionmentioning
confidence: 99%
“…15 An important early change in dementia is the decreased uptake and utilization of glucose by the brain. Greater insulin resistance is associated with decrease in memory and learning capabilities 16 .…”
Section: Introductionmentioning
confidence: 99%